Uwarunkowania powstania i funkcjonowania torfowiska przejściowego w dolinie Wilczej Strugi w zlewni Wdy Determinant factors regarding the development and functioning of transition peatland in the Wilcza Struga valley of the Wda catchment area - Danuta Szumińska (Kazimierz Wielki University, 2015)
Szumińska Danuta. Uwarunkowania powstania i funkcjonowania torfowiska przejściowego w dolinie Wilczej Strugi w zlewni Wdy = Determinant factors regarding the development and functioning of transition peatland in the Wilcza Struga valley of the Wda catchment area. Journal of Education, Health and Sport. 2015;5(5):165-172. ISSN 2391-8306. DOI 10.5281/zenodo.17489 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A165-172 https://pbn.nauka.gov.pl/works/559350 http://dx.doi.org/10.5281/zenodo.17489 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.04.2015. Accepted: 08.05.2015.   Uwarunkowania powstania i funkcjonowania torfowiska przejściowego w dolinie Wilczej Strugi w zlewni Wdy   Determinant factors regarding the development and functioning of transition peatland in the Wilcza Struga valley of the Wda catchment area   Danuta Szumińska   Instytut Geografii, Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy, email: dszum@ukw.edu.pl   Słowa kluczowe: sandr Wdy, warunki hydrogeologiczne, torfowisko przejściowe. Key words: the Wda outwash plain, hydrogeological conditions, transition peatland.   STRESZCZENIE. Badania przeprowadzono w obrębie niewielkiego torfowiska, zlokalizowanego w środkowej części zlewni Wdy, w strefie przejściowej pomiędzy sandrem Wdy a Wysoczyzną Świecką. Obszar ten charakteryzuje się niewielką jeziornością, natomiast znaczną liczbą torfowisk.  Analizowane torfowisko położone jest w niewielkiej dolince, odwadnianej w kierunku Wdy przez ciek, któremu nadano na potrzeby artykułu nazwę Wilcza Struga. Wypływa on z mokradła, wykształconego w rynnie, która rozcina powierzchnię morenową Wysoczyzny Świeckiej. Na podstawie analizy budowy geologicznej torfowiska i jego otoczenia stwierdzono, że powstało ono w zagłębieniu zlokalizowanym na linii odpływu fluwioglacjalnego, możliwe że na linii wcześniejszej rynny glacjalnej lub subglacjalnej. Przetrwanie zagłębienia było możliwe dzięki konserwacji martwym lodem. Świadczy o tym obecność pod serią fluwioglacjalną iłów w otoczeniu zagłębienia i brak tych osadów w jego dnie. Bryła była prawdopodobnie przykryta osadami, które zostały później zniszczone w trakcie odpływu fluwioglacjalnego. Złoże torfu o maksymalnej miąższości 4,5 m wypełnia zagłębienie, którego dolna części rozcina osady morenowe, a górna fluwioglacjalne piaski i żwiry. W odległości 100 metrów w kierunku zachodnim przebiega koryto Wilczej Strugi, które znajduje się 0,5 metra niżej niż spąg torfu w zagłębieniu. Torfowisko oddzielone jest od cieku progiem zbudowanym z gliny, który stanowi lokalny dział wód gruntowych. Na podstawie przeprowadzonych obserwacji składu gatunkowego roślinności stwierdzono, że torfowisko reprezentuje aktualnie typ przejściowy. Udział gatunków świadczących o mezotroficznym i oligotroficznym zasilaniu jest większy w centralnej i zachodniej części torfowiska. Gatunki świadczące o zasilaniu wodami eutroficznymi przeważają w części północnej i południowej. Przebieg powierzchniowego działu wodnego zlewni bezpośredniej zagłębienia wyznacza znacznie większą powierzchnię wschodniej części zlewni, przy czym dopływ podziemny z tej strony obejmuje zapewne jeszcze większy obszar. Powoduje to występowanie szerszej strefy eutroficznej poniżej tego zbocza oraz na północnym i południowym krańcu torfowiska - w strefach progów, przez które następuje ucieczka wody w kierunku dna doliny.   ABSTRACT. The study was conducted at a minor peatland located in the middle part of the Wda catchment area, in the transitional zone between the Wda outwash plain and Wysoczyzna Świecka (Fig. 1). The area is characterized by a low lake density index and a significant number of peatlands. The peatland under analysis is found in a small valley drained by a watercourse, for the purpose of the article referred to as Wilcza Struga, towards the Wda river. The watercourse has its source in the wetland formed in a postglacial channel which cuts through the moraine surface of Wysoczyzna Świecka. The geological structure analysis of peatland and the adjacent areas indicates that the peatland had been formed in a depression located along the line of fluvioglacial runoff. It may have been formed over the former glacial or subglacial channel. The depression was preserved with dead ice, as can be concluded from the presence of loam under fluvioglacial series found in its surroundings and lack of these deposits in its bottom. The dead ice block was likely covered with deposits that were later on eroded by fluvioglacial runoff. The hollow is filled with peat having a maximum thickness of 4.5 m. Its upper part cuts through the moraine deposits whereas the lower part incises into fluvioglacial sands and gravels (Fig. 1 and 3). The Wilcza Struga watercourse runs at a distance of 100 m to the west. Its channel lies 0.5 m below the lower-most layer of peat in the depression. The peatland is separated from the water course by a clayey sill, which constitutes a local groundwater divide. Observations of vegetation species composition indicated that the peatland is currently transition. The percentage of species which point at a mesotrophic and oligotrophic supply is higher in the central and western part of the peatland.  Species which indicate a eutrophic supply are prevalent in the northern and southern parts of the area. Surface water divide of the depression catchment area overlaps with a significant surface area of the eastern part of the catchment (Fig. 2), whereas the underground water supply coming from that direction may well cover even larger area. This results in the occurrence of a wider eutrophic zone below the slope and in the northern and southern part of the peatland - in the areas of sills, through which water escapes towards the valley floor.